2016
DOI: 10.1002/adom.201600201
|View full text |Cite
|
Sign up to set email alerts
|

Controlled and Stabilized Light–Matter Interaction in Graphene: Plasmonic Film with Large‐Scale 10‐nm Lithography

Abstract: Graphene-plasmonic metal nanostructures have great potential as optical metamaterials with strong light-matter interactions for applications in energy harvesting, biochemical sensing, and plasmonics. Currently, large-scale fabrication of graphene-plasmonic hybrid systems have the following bottlenecks to realization of their full potential: 1) the geometry of metal nanostructures is not well controlled, 2) the substrates are rigid, and 3) low chemical and thermal stability of plasmonic metal nanostructures. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 103 publications
(105 reference statements)
0
18
0
Order By: Relevance
“…For friction welding, the low efficiency and welding defects are concerning. Alternatively, highpower-density laser has attracted enormous research interest and found its wide application in a broad branch of manufacturing areas including selective laser sintering and three-dimensional printing [1][2][3][4][5][6], surface nanostructuring [7][8][9][10][11][12], multimaterial joining and integration [13][14][15][16][17], material removal [18,19], and mechanical/optical property enhancements [20][21][22][23]. Characteristics, such as contact-free processing, good flexibility and tunablity, high efficiency, and throughput, make laser a feasible route for welding of 42CrMo [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For friction welding, the low efficiency and welding defects are concerning. Alternatively, highpower-density laser has attracted enormous research interest and found its wide application in a broad branch of manufacturing areas including selective laser sintering and three-dimensional printing [1][2][3][4][5][6], surface nanostructuring [7][8][9][10][11][12], multimaterial joining and integration [13][14][15][16][17], material removal [18,19], and mechanical/optical property enhancements [20][21][22][23]. Characteristics, such as contact-free processing, good flexibility and tunablity, high efficiency, and throughput, make laser a feasible route for welding of 42CrMo [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For longer laser pulse durations, the lasting laser radiation will not affect the initial light coupling into metals at the initial state. The essential optical response of nano-to-micro-scale structures improves the coupling capability between laser pulses and colorized samples, [29,45] which serve as the trigger seed for subsequent plasma expansion.…”
Section: Peak Pressure Generation and Residual Stress Distributionmentioning
confidence: 99%
“…This feature of 2D materials can also be used in SERS substrate development 42,46 . When single layer graphene combines with Ag nanostructure, the hybrid SERS platform provides both better SERS performance and excellent stability in a harsh environment (sulfur) and at high temperatures (300 °C) 47 . Liu at al.…”
Section: Stabilitymentioning
confidence: 99%